Comparison of the Clinical Profile and Complications of Mixed Malarial Infections of Plasmodium Falciparum and Plasmodium Vivax versus Plasmodium Falciparum Mono-infection - Vivek Joseph; Muralidhar Varma; Sudha Vidhyasagar; Alvin Mathew (Sultan Qaboos University Medical Journal, 2011)
Objectives: This study aimed to compare the clinical presentations and complications in patients having mixed malaria infection of Plasmodium falciparum and Plasmodium vivax with those of patients with malaria due to a P. falciparum mono-infection. Methods: The medical records of malaria patients admitted to Kasturba Medical College, Manipal, India, during the years 2008–10 were analysed. Inclusion criteria were patients in whom P. falciparum and P. vivax coinfection or P. falciparum mono-infection alone was confirmed on peripheral smear examination. Exclusion criteria were patients in whom P. vivax infection alone was diagnosed on peripheral smear examination. The sample size was twenty patients diagnosed with mixed infection of P. falciparum and P. vivax and 60 patients diagnosed with P. falciparum mono-infection. Results: 35% of mixed infections had thrombocytopenia as compared to 51.7% of P. falciparum mono-infections. A total of 5% of the mixed infections had renal failure as compared to 16.7% of the falciparum mono-infections. Total bilirubin was raised in 15.8% of mixed infections and in 46.6% of falciparum mono-infections. Abnormal liver enzymes were seen in 36.8% of mixed infections and in 66.6% of falciparum mono-infections. None of the mixed infections had a parasite index over 2% while it was present in 28% of the falciparum mono-infections. Conclusion: Patients with mixed infections were found to have a lower incidence of severe complications such as anaemia, thrombocytopenia, liver and renal dysfunction and a lower parasite index. Thus mixed malaria tends to have a more benign course as compared to malaria due to P. falciparum mono-infection.